Inner ear morphometry on high resolution computed tomography in patients with sensorineural hearing loss - Jahanbakhsh, Javid (2016)

(untitled)
Materials and methods: A retrospective study was conducted from May 2012 till August 2015 in the Department of Radiology, Hospital Universiti Sains Malaysia. Patients with sensorineural hearing loss who was referred for computed tomography of the temporal bone were selected in the study group. All scans were performed on Siemens 128-slices CT scanner Somatom Definition 128-slice with high-resolution scanning protocol. All the images were reconstructed to bone window. Patient who had computed computed tomography of the temporal bone for other indications with normal contralateral ear were taken as a control group. Three inner ear structures (vestibular width, cochlear basal turn and lateral semicircular canal bony island width) were measured on axial image on diagnostic workstation). The measurements were repeated three times and average of these measurements were taken. Measurements were randomly selected and validated by an experienced radiologist to minimize bias. Results: Fifty ears from 28 patients with SNHL (22 patients with bilateral disease and 6 patients with unilateral) were included in this study. Gross abnormality of inner ear detected on HRCT in 5 ears (3 patients) of SNHL were excluded. A total of 45 ears were selected in both study and control groups. Twenty-five ears from patients with SNHL were male patient and 20 ears were female, same as control group. Age range for patients with SNHL was 2 to 23 years old with mean of 9.98 years old. The age range for control group was 2 to 76 years old with mean of 29.55 years. The mean (standard deviation) width of cochlear was 0.190 cm (0.017 cm), vestibular was 0.330 cm (0.039 cm) and lateral semicircular bone island width was 0.362cm (0.566 cm) of patients with SNHL. There were no significantly different of mean of these measurements with control group (P value > 0.05). Conclusions: The morphometry of cochlear, vestibular and lateral semicircular bone island width are not reliably differentiating between SNHL and non SNHL patients.